2018
DOI: 10.1021/acs.jcim.7b00708
|View full text |Cite
|
Sign up to set email alerts
|

Combining Stochastic Deformation/Relaxation and Intermolecular Contacts Analysis for Extracting Pharmacophores from Ligand–Receptor Complexes

Abstract: We previously combined molecular dynamics (classical or simulated annealing) with ligand-receptor contacts analysis as a means to extract valid pharmacophore model(s) from single ligand-receptor complexes. However, molecular dynamics methods are computationally expensive and time-consuming. Here we describe a novel method for extracting valid pharmacophore model(s) from a single crystallographic structure within a reasonable time scale. The new method is based on ligand-receptor contacts analysis following ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…It has been reported that the spike glycoprotein of SARS-CoV-2 is modified via homologous recombination and is a mixture of bat SARS-CoV and an unknown Beta-CoV [3,32]. Superimposition of the cryo-EM structure of the RBD of SARS-514 CoV-2 onto a previously reported SARS RBD structure revealed a root-mean-square deviation (RMSD) of 3.8 Å over 959 Cα atoms [2], which indicates highly similar 3D protein structures [63][64][65].…”
Section: Is Ace2 the Receptor For S Protein?mentioning
confidence: 80%
“…It has been reported that the spike glycoprotein of SARS-CoV-2 is modified via homologous recombination and is a mixture of bat SARS-CoV and an unknown Beta-CoV [3,32]. Superimposition of the cryo-EM structure of the RBD of SARS-514 CoV-2 onto a previously reported SARS RBD structure revealed a root-mean-square deviation (RMSD) of 3.8 Å over 959 Cα atoms [2], which indicates highly similar 3D protein structures [63][64][65].…”
Section: Is Ace2 the Receptor For S Protein?mentioning
confidence: 80%
“…The fundamental use of pharmacophores models is the discovery of new chemical scaffolds demonstrating similar biological characteristics or scaffold hopping [56][57][58][59][60][61][62][63][64][65][83][84][85]. Therefore, Refined-Hypo (SB-1) pharmacophore (Figure 2) was used as a 3D query to search and screen the NCI list of compounds for new Aurora-A kinase inhibitors with novel chemotypes.…”
Section: In-silico Screening and Fret Based Enzyme Inhibition Assaymentioning
confidence: 99%
“…Distance evaluations were automatically performed employing a tailored-made Fortran-based soware. [24][25][26][47][48][49] Accordingly, each docking-scoring conguration is used to build a 2D matrix, such that each matrix is composed of row labels corresponding to docked ligands and column labels corresponding to different binding site atoms. The matrix is lled with binary code, whereby "zeros" correspond to interatomic distances that exceed the predetermined threshold (of 2.5 A) and "ones" for distances below (or equal) the predened 2.5 A threshold cutoff.…”
Section: Methodsmentioning
confidence: 99%
“…25 It proceeds by either mapping out all binding site atoms that contact a list of docked potent ligands and evade inactive ones, [24][25][26]57 or identify binding site atoms that frequently contact certain bound ligand during molecular dynamics or related simulations. [47][48][49] Machine learning (ML) is the implementation of statistical approaches for learning and predicting properties. 27,28 Supervised ML attempts to build predictive model(s) based on data collected from input and output sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation